2018
DOI: 10.4103/iju.iju_218_17
|View full text |Cite
|
Sign up to set email alerts
|

Utility of restage transurethral resection of bladder tumor

Abstract: Introduction:Transurethral resection of bladder tumor (TURBT) aims at complete resection of all the visible tumors. Existing guidelines recommend restage TURBT in all patients with T1 and high-grade tumors, to avoid under-staging. However, restage TURBT may not be plausible/feasible at all the times. This study was performed with an aim to better define the utility of restage TURBT in a tertiary care hospital of India.Methods:Patients with high grade/T1 tumors at the first TURBT were prospectively enrolled. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
(9 reference statements)
0
0
0
Order By: Relevance
“…Despite this, TURBT still presents significant limitations for the treatment of BC, namely incorrectly staging the tumor due to inadequate resection, the high risk of recurrence especially in higher grades of BC, the invasiveness of the surgery, and the risk of not detecting smaller malignancies that are not visible during the procedure [27,53]. Indeed, a second resection is recommended by the European Association of Urology for T1 and HG tumors due to their high likelihood of cancer progression [55]. It has been shown that performing a second resection before introducing the BCG therapy significantly decreases the risk of cancer recurrence [56].…”
Section: Turbt and Radical Cystectomymentioning
confidence: 99%
“…Despite this, TURBT still presents significant limitations for the treatment of BC, namely incorrectly staging the tumor due to inadequate resection, the high risk of recurrence especially in higher grades of BC, the invasiveness of the surgery, and the risk of not detecting smaller malignancies that are not visible during the procedure [27,53]. Indeed, a second resection is recommended by the European Association of Urology for T1 and HG tumors due to their high likelihood of cancer progression [55]. It has been shown that performing a second resection before introducing the BCG therapy significantly decreases the risk of cancer recurrence [56].…”
Section: Turbt and Radical Cystectomymentioning
confidence: 99%